Vertical distribution of microplastics in bay sediment reflecting effects of sedimentation dynamics and anthropogenic activities. (March 2020) - Zheng, Yifan; Li, Jingxi; Cao, Wei; Jiang, Fenghua; Zhao, Chang; Ding, Haibing; Wang, Menghui; Gao, Fenglei; Sun, Chengjun
Abstract: Microplastics are ubiquitous in our environment, yet we have little knowledge on their accumulation profile and changing trend. In this study, we selected the semi-enclosed Jiaozhou Bay as the research area to study the vertical distribution characteristics of microplastic in the sediment and analyzed factors that might affect this distribution pattern. We found six different polymer types and the microplastic abundance ranged between 2.5 items/kg d.w.-27.5 items/kg d.w.. Microplastic abundance was very low in deep sediment and generally showed a decreasing trend from the surface down with some shifts at different depth at certain sites. Based on our data, the total microplastics in the sediment were estimated to reach 3.71 tons in Jiaozhou Bay. This study shows that the vertical microplastic abundance profile in the sediment can not only show the microplastics pollution level but also reflect environmental factors and anthropogenic impacts. Graphical abstract: Unlabelled Image Highlights: Sediment microplastics show chronological periodicity with depth in Jiaozhou Bay. The dominant microplastic in Jiaozhou Bay sediment cores were rayon, PET and PE. The water dynamic and sedimentation rate affect microplastic deposition. Anthropogenic activities affect microplastics distribution in the bay sediment.